PERTANGGUNGJAWABAN PIDANA TERHADAP ANAK YANG MELAKUKAN TINDAK PIDANA BERAT DIKAJI DARI PERSPEKTIF HUKUM POSITIF INDONESIA - silalahi, gabe horas; Jamba, Padrisan (SCIENTIA JOURNAL, 2023)
ABSTRACTThe juvenile justice system has been regulated in Law Number 11 of 2012 which states that children between the ages of 12 and under 18 are considered children in conflict with the law. Juvenile criminal justice is different from the general criminal justice system that applies in Indonesia. There are various factors, such as psychological and sociological factors, which can cause a child to be considered guilty of a crime. In this system, accountability for crimes committed by children prioritizes the principles of restorative justice. This study aims to understand the legal provisions that apply to children who are involved in serious crimes and to see how the form of accountability for these crimes is seen from the perspective of positive law in Indonesia. This study uses a normative juridical method by conducting literature studies related to legal arrangements related to children and analyzing them descriptively to develop the core problems in this writing. The results of the research show that Law Number 11 of 2012 concerning the Juvenile Criminal Justice System has regulated special legal provisions for children as criminal offenders. Children in this system have the right to receive special treatment during the investigation, prosecution and trial process so that their mental condition is maintained. In addition, the form of juvenile criminal responsibility is also based on the age of the child, and the juvenile justice system places more emphasis on restorative justice approaches and settlement through diversion.Keywords: Children, Criminal, Diversion, Justice, Responsibility,.